202k views
0 votes
5x-4=-3-x so ya can yall help

User Embedded
by
4.0k points

2 Answers

5 votes

Explanation:

5x-4=-3-x

5x+x=4+(-3)

6x=1

x=1/6

User Kireeti K
by
4.6k points
6 votes

Answer:


\boxed{ \huge{ \bold{ \sf{x = 0.16}}}}

Explanation:


\sf{5x - 4 = - 3 - x}

Move constant to R.H.S and change it's sign

Similarly, Move variable to L.H.S and change it's sign


\sf{5x + x = - 3 + 4}

Collect like terms


\sf{6x = - 3 + 4}

Calculate


\sf{6x = 1}

Divide both sides of the equation by 6


\sf{ (6x)/(6) = (1)/(6) }

Calculate


\sf{x = 0.16}

Hope I helped!

Best regards!!

User Makson
by
4.6k points